2013
DOI: 10.2141/jpsa.0120083
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Avian Genetic Resources

Abstract: Conservation of avian genetic resources is important, as 13.0% (1,313/10,064) of known avian species are currently categorized as endangered by the International Union for Conservation of Nature and Natural Resources (IUCN, 2012). Development of an integrated system for conservation of avian genetics is necessary; however, germplasm conservation systems developed for mammals cannot be applied directly to avians, primarily due to the unique anatomical and physiological characteristics of the avian egg. Thus an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
1
11
0
1
Order By: Relevance
“…The results were in line with the results reported by Nakajima et al (2011;2013) in White Leghorn (WL) and Rhode Island Red (RIR) chickens. The result also confirmed that PGCs isolation from gonad was easier and better with larger number of collected PGCs compared to the isolation of circulated PGCs.…”
Section: µM 100 µMsupporting
confidence: 91%
See 1 more Smart Citation
“…The results were in line with the results reported by Nakajima et al (2011;2013) in White Leghorn (WL) and Rhode Island Red (RIR) chickens. The result also confirmed that PGCs isolation from gonad was easier and better with larger number of collected PGCs compared to the isolation of circulated PGCs.…”
Section: µM 100 µMsupporting
confidence: 91%
“…The unique migration pathway of PGCs provides a possibility to isolate subsequent PGCs based on their locations. Primordial germ cells can be isolated from X-stage blastoderm, blood at 2.5-3-day-old embryos (stages 13-17 HH), or gonads at 5.5-6-day-old embryos (stages 26-28 HH) (Chojbacka-Puchta et al, 2012;Tajima, 2013). Numerous studies had reported the isolation and collection of PGCs from gonadal embryos (Nakamura et al, 2011;Nakajima et al, 2011;Nakajima et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Primordial germ cells (PGCs) are progenitor cells of ova and spermatozoa and are one of the most appropriate cells for germline manipulation in chickens (Kuwana, 1993;Tajima, 2002Tajima, , 2013Naito, 2003Naito, , 2015. Exogenous DNA could be introduced transiently into the gonads of recipient embryos by transfecting freshly collected PGCs in vitro and then transferring them to recipient embryos (Naito et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Preservation of avian genetic resources was, therefore, conducted only by preserving spermatozoa (Tajima, 2013), and preservation of female gametes was impossible.…”
Section: Conservation Of Genetic Resourcesmentioning
confidence: 99%
“…These techniques have been improved and established as a system for chicken germline manipulation. The author reviewed the progress of chicken embryo manipulation (Naito, 2003a, b, c), and further progress in this field has been reported in recent reviews (Lavial et al, 2006;Lavial and Pain, 2010;Han, 2009;Glover and McGrew, 2012;Intarapat and Stern, 2013;Nakamura et al, 2013;Nishijima and Iijima, 2013;Park et al, , 2014Tajima, 2013). This review, therefore, focuses on several topics involved in chicken embryo manipulation.…”
Section: Introductionmentioning
confidence: 99%